2022
DOI: 10.3310/htaf1569
|View full text |Cite
|
Sign up to set email alerts
|

Hospital at Home admission avoidance with comprehensive geriatric assessment to maintain living at home for people aged 65 years and over: a RCT

Abstract: Background Evidence is required to guide the redesign of health care for older people who require hospital admission. Objectives We assessed the clinical effectiveness and cost-effectiveness of geriatrician-led admission avoidance hospital at home with comprehensive geriatric assessment, the experiences of older people and their caregivers, and how the services differed. Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…Despite innovations in international healthcare systems seeking to expand the application of CGA [17,18,45], older adults and caregivers' level of participation in the management of acute illness and their interface with HCPs is not always recognised [46,47]. Our ndings draw parallels with those outlined in a scoping review of 13 studies, which explored informal caregivers' views on their perceived levels of involvement in collaborative discussions with HCPs [48].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Despite innovations in international healthcare systems seeking to expand the application of CGA [17,18,45], older adults and caregivers' level of participation in the management of acute illness and their interface with HCPs is not always recognised [46,47]. Our ndings draw parallels with those outlined in a scoping review of 13 studies, which explored informal caregivers' views on their perceived levels of involvement in collaborative discussions with HCPs [48].…”
Section: Discussionmentioning
confidence: 77%
“…Qualitative research has identi ed important contradictions between the aims of CGA and patients' experiences, for example, a study, which explored older adults' experiences of CGA in an outpatient setting, revealed a dominant focus on illness symptoms and limitations related to ageing [16]. It is increasingly important to understand older adults' perspectives as international healthcare systems continue to evolve and recon gure to meet increased demand for resources [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…We included eight core documents from the first search [ 16 , 17 , 32–37 ] and 20 documents from stage 2 (nine peer-reviewed [ 15 , 30 , 38–44 ] and 11 grey literature [ 6 , 28 , 29 , 45–52 ]). Ten documents report on four studies [ 15–17 , 29 , 30 , 36–38 , 44 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, although it is true that an economic evaluation of the program has not been carried outwhich is one of the limitations of our study-it can be assured that while in specialized care, the program resulted in savings, in primary care, the costs would have increased due to the increase in home visits. The difference has been found to be cost-effective when related to avoided hospital admissions (33,46).…”
Section: Discussionmentioning
confidence: 99%